Downbeat nystagmus: a clinical and pathophysiological review - Marcelli, Vincenzo; Giannoni, Beatrice; Volpe, Giampiero; Faralli, Mario; Fetoni, Anna Rita; Pettorossi, Vito E. (Frontiers in Neurology, 2024)
Downbeat nystagmus (DBN) is a neuro-otological finding frequently encountered by clinicians dealing with patients with vertigo. Since DBN is a finding that should be understood because of central vestibular dysfunction, it is necessary to know how to frame it promptly to suggest the correct diagnostic-therapeutic pathway to the patient. As knowledge of its pathophysiology has progressed, the importance of this clinical sign has been increasingly understood. At the same time, clinical diagnostic knowledge has increased, and it has been recognized that this sign may occur sporadically or in association with others within defined clinical syndromes. Thus, in many cases, different therapeutic solutions have become possible. In our work, we have attempted to systematize current knowledge about the origin of this finding, the clinical presentation and current treatment options, to provide an overview that can be used at different levels, from the general practitioner to the specialist neurologist or neurotologist.